CHAIR’S WELCOME (EAAE Annual Conference Proceedings, 2025)
The Barcelona School of Architecture approaches architecture not just an academic discipline – but as an ongoing dialogue with the world. Like many European architecture schools, ETSABUPC thrives on a profound and evolving relationship with the practice of architecture. Here, teaching is not a simple transfer of knowledge, but the dynamic fusion of thoughtful critique and hands-on experimentation that meets society’s ever-shifting demands.